Analisis Kontribusi, Efektivitas dan Efisiensi Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten Alor - Gisela Lobang; Petrus E. de Rozari; Maria Indriyani Hewe Tiwu (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This study aims to analyze the contribution, effectiveness and efficiency of the tourism sector to local revenue in Alor Regency. This research is a quantitative descriptive study with time series data for 5 years, namely in the 2018-2022 period. The data used are tourism sector revenue realization data, local revenue realization data, tourism sector revenue target data and tourism sector spending data sourced from the Alor Regency Regional Revenue Agency and the Alor Regency Tourism Office. To calculate the contribution, the level of effectiveness and the level of efficiency of the tourism sector to the local revenue of Alor Regency the analysis technique used is to calculate the Contribution Ratio, Effectiveness Ratio and Efficiency Ratio. The results of this study indicate that the contribution made by the tourism sector to local revenue in Alor Regency for the period 2018-2022 is very less which results in this contribution being ineffective and inefficient.